Recent Experimental Research on Short Story Effectiveness in EFL Classrooms: A Review - Pardede, Parlindungan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
In the past decades, there has been a strong belief that short stories are powerful pedagogical tool educators can use to help EFL students optimize their learning, Much has been said about short stories’ effectiveness in the reinforcement of language skills development and language components learning. They are also claimed to be more effective than other materials and tools to empower EFL students to use English in socially and culturally appropriate ways as they facilitate students to engage with rich, authentic target language uses (Cameron, 2001) and offer motivating source to transmit information and ideas, nurture values and beliefs, and convey subliminal messages (King, 2001). Yet, available studies still lack essentials like what specific aspects of EFL learning have profited from short story use and how short story efficacies were exactly measured. This review aims at exploring the trend in 35 experimental research on short stories use in EFL classrooms published in 2011-2020, what they say about short stories efficacy, and the identified gaps that future research needs to address. The results will hopefully provide teachers, researchers, curriculum designers, and policymakers with a clearer understanding of short stories use in EFL classrooms.